2023
DOI: 10.3389/fpls.2023.1215044
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA-mediated competing endogenous RNA regulatory network during flower development and color formation in Melastoma candidum

et al.

Abstract: M. candidum, an evergreen shrubby flower known for its superior adaptation ability in South China, has gained increased attention in garden applications. However, scant attention has been paid to its flower development and color formation process at the non-coding RNA level. To fill this gap, we conducted a comprehensive analysis based on long non-coding RNA sequencing (lncRNA-seq), RNA-seq, small RNA sequencing (sRNA-seq), and widely targeted metabolome detection of three different flower developmental stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…The significance of lncRNA in diverse biological processes is crucial in plant kingdoms, which can modulate the expression of target genes through cis ‐ and trans ‐acting mechanisms; impact the structure and function of chromatin; and participate in RNA transcription, splicing and stabilization (Zheng et al ., 2023 ). Several studies have illustrated the significance of lncRNAs in plant development and colour formation process (Li et al ., 2023 ; Zheng et al ., 2023 ). In this study, two Blp_lncRNAs were identified to be significantly co‐expressed with HvBlp , which may be involved in the stage‐ and tissue‐specific expression of HvBlp .…”
Section: Discussionmentioning
confidence: 99%
“…The significance of lncRNA in diverse biological processes is crucial in plant kingdoms, which can modulate the expression of target genes through cis ‐ and trans ‐acting mechanisms; impact the structure and function of chromatin; and participate in RNA transcription, splicing and stabilization (Zheng et al ., 2023 ). Several studies have illustrated the significance of lncRNAs in plant development and colour formation process (Li et al ., 2023 ; Zheng et al ., 2023 ). In this study, two Blp_lncRNAs were identified to be significantly co‐expressed with HvBlp , which may be involved in the stage‐ and tissue‐specific expression of HvBlp .…”
Section: Discussionmentioning
confidence: 99%
“…By constructing competitive endogenous RNA (ceRNA) networks of lncRNAs and circRNAs in mice with different coat colors, complex interactions between ncRNAs and messenger RNAs (mRNAs) related to skin and melanocyte development were discovered, which co-regulate pigmentation development [11]. Whole-transcriptome sequencing and broadly targeted metabolome analysis of circRNAs, mRNAs, and small RNAs (sRNAs) of Melastoma candidum at three different developmental stages led to the construction of nine circRNA-mediated ceRNA regulatory networks that demonstrated important roles in M. candidum flower development and color formation [12]. In fungi, ncRNAs, such as lncRNA and micro-RNA-like (milRNA) molecules are involved in cell division, nutrient perception, sexual reproduction, and other processes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%